Predictive value of Body Mass Index (BMI) and Determination of optimum Cut-off Point in the diagnosis of endometrial hyperplasia in Pre-menopausal women with abnormal uterine Bleeding - Sara Alizadeh Garna; Shahla Yazdani; Hadis Mosavi; mohammad ranaei; Karimollah Hajian-Tilaki; Zinatossadat Bouzari (Caspian Journal of Internal Medicine, 2024)
Background: The suitable BMI cut-off point in persons with endometrial cancer or hyperplasia with abnormal uterine bleeding was investigated in this study. Methods: This case-control research was conducted on 1470 women with abnormal uterine bleeding in Ayatollah Rouhani Hospital,Babol between 2010 and 2012, with 312 participants included in the study. In terms of uterine biopsy results, patients were split into six groups: simple hyperplasia without atypia, simple hyperplasia with atypia, complicated hyperplasia with atypia, complex hyperplasia without atypia, endometrial cancer, and normal persons. Results: The mean age and BMI of patients in these three groups were not significantly different (P equal to 0.081 and 0.435, respectively). The kind of disease exhibited a strong relationship with menstruation (P 0.001). The body mass index (BMI) values ​​did not have significant levels under the curve to determine the appropriate cut-off point in the diagnosis of hyperplasia plus endometrial cancer and endometrial cancer alone (P 0.380 and 0.124, respectively) and hyperplasia alone (P = 0.920). Based on logistic regression, age 50 years and older and irregular menstruation were significant with OR equal to 2.36 and 2.09 (P = 0.011) and HTN with OR equal to 0.44 (P = 0.026), respectively. Conclusion: BMI has little predictive value in the detection of endometrial cancer or hyperplasia, according to the findings, and other diagnostic and screening modalities should be utilized instead. The findings backed up the theory that old age and irregular menstruation are linked to an increased risk of endometrial cancer.